SmI2-mediated dimerization of indolylbutenones and synthesis of the myxobacterial natural product indiacen B - Marsch, Nils; Jones, Peter G.; Lindel, Thomas (Beilstein Journal of Organic Chemistry, 2015)
The synthesis and reactivity of indole derivatives substituted in the benzene section was studied. Starting materials 4- and 6-iodoindole were conveniently prepared via the Batcho–Leimgruber route and purified by sublimation. Novel vicinally indolyl-substituted cyclopentanols with unexpected cis-configuration were formed by SmI2-mediated reductive dimerization of a 4-(indol-6-yl)butenone, obtained by Heck reaction. The two indolyl units appear to chelate Sm(II)/(III) leading to a gauche-type arrangement at the newly formed bond between the two β-carbons. Through a sequence of Sonogashira cross coupling and Meyer–Schuster rearrangement 6-prenoylindole was synthesized and reductively dimerized to a cyclopentane in a [3 + 2] cycloaddition by treatment with SmI2 in THF. From 4-iodoindole, the natural product indiacen B from the myxobacterium Sandaracinus amylolyticus was synthesized for the first time, confirming its antimicrobial activity. The E-configuration of the chloroalkene moiety of indiacen B was confirmed by X-ray analysis.
Keywords: biological evaluation; heterocycles; indoles; natural products; total synthesis